Kualitas Layanan Malang City Tour dalam Meningkatkan Jumlah Wisatawan di Kota Malang - Khaulatur Rizkiya; Retno Wulan Sekarsari; Didik Supriyanto (Idarotuna : Journal of Administrative Science, 2025)
This study was conducted to examine the service quality of Malang City Tour (MACITO) in increasing the number of tourists in Malang City. MACITO is a free tourist transportation service provided by the Malang City Government as a public service innovationin the world of tourism. The service is expected to provide a pleasant travel experience while supporting the city’s image as an attractive tourist destination. This research was conducted using a qualitative, descriptive approach through data collection from interviews, observations, and document analysis.The analysis is based on the ServQual model, which measures service quality across five dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The findings reveal that MACITO service quality is considered fairly good, particularly in terms of vehicle comfort, cleanliness of facilities, and staff friendliness, which create a sense of safety and convenience for tourists. Nevertheless, several challenges remain, including the online booking system that is still under improvement, and queuing facilities that are less comfortable at certain departure points. Despite these issues, tourists generally have positive perceptions of MACITO as it supports mobility and adds value to their travel experience. Therefore, this study recommends optimizing the utilization of existing fleets, accelerating the improvement of digital service systems, and enhancing the comfort of queuing facilities to further improve service quality and attract more tourists.